1971
DOI: 10.1037/h0030672
|View full text |Cite
|
Sign up to set email alerts
|

Limbic-diencephalic mechanisms of voluntary movement.

Abstract: Data from a series of brain-behavior experiments utilizing techniques of ablation, ICS, and electrical recording emphasize the importance of the concept of levels of function in understanding behavior. Initiation, performance, and cessation of voluntary behaviors (e.g., walking, manipulating objects) are associated with activation of ascending pathways from the diencephalon to the hippocampus and neocortex. More automatic behaviors (e.g., chewing, emotional expression) are not directly dependent on these pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
149
0

Year Published

1974
1974
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(168 citation statements)
references
References 165 publications
19
149
0
Order By: Relevance
“…The hippocampus shows two differen-tiable states during which the intrahippocampal EEG shows very different characteristics [24,150,229]. One state, called theta, shows a profound 7 -10 Hz rhythm [150,229] with a higher 40 Hz rhythm (called gamma) riding above it [18] and occurs during movement and other attentive behaviors [229]. During theta, cellular activity tends to be smooth; a relatively constant proportion of hippocampal pyramidal cells fire spikes, with each cell firing on the order of a second or two [94,150,169].…”
Section: A1 Hippocampal Representational Replaymentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus shows two differen-tiable states during which the intrahippocampal EEG shows very different characteristics [24,150,229]. One state, called theta, shows a profound 7 -10 Hz rhythm [150,229] with a higher 40 Hz rhythm (called gamma) riding above it [18] and occurs during movement and other attentive behaviors [229]. During theta, cellular activity tends to be smooth; a relatively constant proportion of hippocampal pyramidal cells fire spikes, with each cell firing on the order of a second or two [94,150,169].…”
Section: A1 Hippocampal Representational Replaymentioning
confidence: 99%
“…During theta, cellular activity tends to be smooth; a relatively constant proportion of hippocampal pyramidal cells fire spikes, with each cell firing on the order of a second or two [94,150,169]. The other state, called LIA (large-amplitude irregular activity) shows a noisier EEG punctuated by occasional 100 ms sharp-wa6es with a 200 Hz rhythm riding on them [25,150,229,249]. Cellular activity in LIA is usually quiet, with strong bursts of activity during the sharp-waves [25,94,150,169].…”
Section: A1 Hippocampal Representational Replaymentioning
confidence: 99%
“…In this context, it is useful to consider what Vanderwolf (1967Vanderwolf ( , 1971 modify the trigger mechanisms by which one response system or motor set gives way to another. Such an impairment would make an ongoing response less amenable to being "switched," and thus less likely to yield precedence to another response .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand , Van Hoesen and his coworkers (Van Hoesen, MacDougall, & Mitchell , 1969 ;Wilson, Mitchell, & Van Hoesen, 1972) reported that habenular lesions impaired food-related passive avoidance , while enhancing two-way shuttle box avoidance perform ance. Large medial thalamic lesions, which included damage to the habenula, have been found to severely impair one-way active avoidance acquisition (Delacour, ' 1971 ;Vanderwolf, 1967Vanderwolf, , 1971, although Delacour (1971) stated that lesions limited to the habenular complex did not result in impairment in this task. Nevertheless, Tigner (1972) has reported impairment in one-way avoidance learning after lesions restricted to either the habenular nucleus or the dorsornedial thalamus.…”
mentioning
confidence: 99%
“…Additionally, some investigators report that tests of spatial memory are sensitive to MDN damage (Means et al 1975;Kessler et al 1982;Stokes andBest 1988, 1990), although others report no effect on such tasks (Hunt and Aggleton 1991). The effects of MDN damage have been interpreted variously as affecting primarily the early, encoding stages of learning (e.g., Gabriel et al 1989;Hunt and Aggleton 1991), working memory (e.g., Gaffan and Murray 1990;Gaffan and Watkins 1991;M'Harzi et al 1991), or other more nonspecific activity, such as motor processes (Vanderwolf 1971;Vives and Mogensen 1985;Swerdlow and Koob 1987;Ray and Price 1992), attentional phenomena (Stokes and Best 1990;Bouyer et al 1992), or autonomic mechanisms (West and Benjamin 1983;Buchanan and Powell 1986;Huang et al 1988;. Devinsky et al (1995) suggested recently that the MDN projection cortex (referred to by these authors as anterior cingulate cortex, but which we have termed the medial prefrontal cortex; mPFC) is important for visceromotor control, and may also participate in a response selection process, particularly in situations requiring novel response choices.…”
Section: Powell and Churchwellmentioning
confidence: 99%